A Preliminary Study of the Safety of Red Light Phototherapy of Tissues Harboring Cancer - Myakishev-Rempel, Max (Mary Ann Liebert, Inc., 2012)
Objective: Red light phototherapy is known to stimulate cell proliferation in wound healing. This study investigated whether low-level light therapy (LLLT) would promote tumor growth when pre-existing malignancy is present. Background data: LLLT has been increasingly used for numerous conditions, but its use in cancer patients, including the treatment of lymphedema or various unrelated comorbidities, has been withheld by practitioners because of the fear that LLLT might result in initiation or promotion of metastatic lesions or new primary tumors. There has been little scientific study of oncologic outcomes after use of LLLT in cancer patients. Methods: A standard SKH mouse nonmelanoma UV-induced skin cancer model was used after visible squamous cell carcinomas were present, to study the effects of LLLT on tumor growth. The red light group (n=8) received automated full body 670 nm LLLT delivered twice a day at 5 J/cm(2) using an LED source. The control group (n=8) was handled similarly, but did not receive LLLT. Measurements on 330 tumors were conducted for 37 consecutive days, while the animals received daily LLLT. Results: Daily tumor measurements demonstrated no measurable effect of LLLT on tumor growth. Conclusions: This experiment suggests that LLLT at these parameters may be safe even when malignant lesions are present. Further studies on the effects of photoirradiation on neoplasms are warranted.